DEVELOPMENT OF HANDOUT TEACHING MATERIALS ON THE MATERIAL OF FINDING INVITATIONS IN PERSUASIVE TEXTS FOR STUDENTS IN CLASS VIII OF SMP NEGERI 4 LAHEWA - Nazara, Edieli; Zega, Imansudi; Riana, Riana; Ndruru, Mastawati (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2024)
The purpose of this study was to develop handout teaching materials on the material of finding invitation sentences in persuasive texts that are feasible, practical and effective. This type of research is development research using the ADDIE model consisting of Analysis, Design, Development, Implementation, Evaluation. The research instruments used were validation questionnaires from material experts, language experts, and design experts, as well as student response questionnaires and effectiveness on student learning outcomes. The results of this study were the development of handout teaching materials on finding invitation sentences in persuasive texts. The results have met the criteria of very feasible, namely the results of the assessment of material experts in revision I with an achievement of 52% and revision II with an achievement of 88%. The results of the assessment of language experts in revision I with an achievement of 52% and revision II with an achievement of 93%. The results of the assessment of design experts in revision I with an achievement of 56% and revision II with an achievement of 84%. The results of practicality in small group trials reached 90% and field trials reached 92% with very practical criteria. The effectiveness results in small group trials reached 100% and in field trials reached 87.5% with very good and effective criteria. From the results of the study above, the development of handout teaching materials is feasible, practical and effective to use in the learning process.